Rust Phase Transformation In The Presence Of Mangrove Tannins. - A.Rahim, Afidah; Musa, Noor Hamdah; Adnan, Rohana; Kassim, M.Jain; Rocca, E.; Steinmetz, J. (2006)
The transformation of rust in the presence of 5 g L-1 tannins extracted from mangrove barks was studied.